The Unregistered Child Marriage on Lumbang Society Norm Perspective Legal Pluralism - Ariyanti, Cindy Yulia; Putra, Novandi Dwi (International Journal of Law Dynamics Review, 2024)
Unregistered child marriage has become a custom in the Lumbang community. Nevertheless, the Lumbang community registered their marriage with the State when they had children. The existence of this phenomenon shows that the Lumbang community adopts more than one norm regarding child marriage. This article will reflect on the legal practices in the Lumbang community regarding child marriage. This article is an empirical legal research with a legal anthropology approach. This article uses John Griffith's theory of legal pluralism as a means of uncovering the facts of legal practice in the Lumbang community. This research shows that legal pluralism occurs strongly in the practice of unregistered child marriage in Lumbang. The practice of strong legal pluralism occurs through the incorporation of religion-adult law, State-adult law, and the distinction of State-adult law. The community conducts unregistered child marriage as a convergence of customary-religious norms as well as divergence of norms due to restrictions on the minimum age of marriage by the State. Then, the State will register the marriage when they have children as a form of convergence of State-adult norms.